2022
DOI: 10.14710/jgi.11.1.49-56
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Valid Tools to Screen Malnutrition in Cancer Patients: A Comparison to Patient Generated-Subjective Global Assessment (PG-SGA)

Abstract: Background: Nutrition screening tools are necessary to predict the risk of malnutrition for cancer patients. Objectives: This study aimed to investigate the validity of nutrition screening tools in identifying malnutrition among cancer patients.Materials and Methods: This cross-sectional study involved 175 oncology patients in Dr. Sardjito General Hospital. Malnutrition risk of participants was screened using Nutrition Risk Screening (NRS) 2002, Simple Nutrition Screening Tool (SNST), Malnutrition Screening To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, the screening results revealed that a higher PG-SGA score indicates a greater risk of malnutrition. Previous studies have revealed that SNST and MST have high sensitivity and specificity for determining cancer patients at risk of malnutrition 30 . This is because both the MST and SNST nutrition screening tools have parameterized questions measuring weight loss and appetite reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the screening results revealed that a higher PG-SGA score indicates a greater risk of malnutrition. Previous studies have revealed that SNST and MST have high sensitivity and specificity for determining cancer patients at risk of malnutrition 30 . This is because both the MST and SNST nutrition screening tools have parameterized questions measuring weight loss and appetite reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence of malnutrition in patients with cancer in Southeast Asia is varied. Individual studies conducted in Indonesia, Malaysia, and Vietnam reported that 50-85% of patients with cancer were at risk of severe malnutrition [13][14][15][16]. Despite this high risk, not every patient with cancer has access to oncology nutrition care provided by nutritionists and dietitians due to limited staffing resources in Southeast Asian countries [17].…”
Section: Introductionmentioning
confidence: 99%